Kiddo Sains AR - Man, Nur Haifa; Hussien, Nur Syahela (Journal of Computing Technologies and Creative Content, 2025)
The Malaysia’s early scientific education is severely lacking in interactive and interesting learning materials for primary level 1 children (ages 7 to 9). To close this gap, Kiddo Sains AR has developed a cutting-edge Augmented Reality (AR) platform that improves science education by using easy, hands-on experiments tailored for young students. The importance of encouraging curiosity, critical thinking, and STEM abilities has grown as Malaysia moves away from traditional tests like the UPSR and towards a more experience-based educational approach. Beyond the confines of traditional classroom environments, Kiddo Sains AR enables children to explore and study science in an interesting and approachable way by converting abstract scientific topics into interactive virtual experiments. The study’s main goals are to create an interesting science platform, analyze the influence of AR-based learning on students’ comprehension and interest in STEM, and determine how effective AR-based learning is. To methodically design, build, and test the platform, the study adheres to the ADDIE instructional design methodology. According to preliminary research, Kiddo Sains AR greatly enhances students’ understanding of scientific concepts and participation. But issues like device compatibility and accessibility need further work. Overall, this study shows how AR could completely transform early scientific education in Malaysia by giving young children more engaging, enjoyable, and productive learning experiences.